JURIDICAL REVIEW RETURN OF PERSONAL PROPERTY PROPERTY AGAINST CONVICTED CRIMINAL ACTS OF CORRUPTION - Ivan Maulana; Waluyo (Universitas Islam Balitar, 2023)
The purpose of this study is to find out what assets can be confiscated in criminal acts of corruption and to find out whether the confiscation of assets carried out by investigators against criminal acts of corruption is in accordance with the rule of law and what legal remedies can be taken to return these assets. In this study, the author uses a normative legal research method using a statutory approach, a case approach, and a conceptual approach. Based on the results of the study, it shows that property that is not the result or instrument of a criminal act of corruption cannot be confiscated unless the convict does not pay replacement money within 1 (one) month after the court decision that has obtained permanent legal force is read, the assets can be confiscated by the prosecutor. and auctioned to cover the replacement money and the confiscation should not be the property that is used as the defendant's livelihood. Legal remedies that can be taken for the convict if the investigator exceeds his authority in carrying out confiscation actions, pretrial legal remedies can be carried out at the investigation stage. Legal remedies for appeal, cassation and review can be carried out if the panel of judges has rendered a decision. A civil lawsuit can be filed if during the confiscation process it is known that assets that are not instruments or proceeds of a criminal act of corruption are also confiscated, causing material and immaterial losses to the plaintiff .